Forecast of the Export of Confectionery Products of Ukraine to food Markets - Baldzhy, Maryna D.; Балджи, Марина Дмитрівна; Nosachenko, Oleksandr; Nezdoyminov, Sergii G.; Нездоймінов, С. Г. (My University, 2021)
Forecasting the development of confectionery industry, allows to consider a picture of perspective functioning of this type of management and to designate the further ways of market development. Realization of the industry export potential is extremely important for the national economy, so it is necessary to determine the main directions of competitive products production that can substantiate management decisions regarding future scenarios of development of market demand for confectionery products and its structure. The article defines the real state and development dynamics of confectionery industry of Ukraine; outlines possible directions of development of foreign economic activity on the already mastered and new perspective markets, improves strategies in unstable and difficult competitive conditions, production planning of competitive goods, which can satisfy demands of foreign and domestic consumers. For forecasting the development of foreign economic activity the statistical method of time series analysis was used, for determining the export dynamics of confectionery industry products directed on establishing regularities in level changes of investigated parameters in time; the main tendency of development of sales in the foreign market are identified. It has been proved that the analysis of time series is the initial basis for estimating tendencies of export development in confectionery production and further construction of export forecasts for market segments. According to the calculations data, the annual increase of export volumes of some kind of products, of confectionery industry for the period of 2021-2023 are predicted. The experience of experimental testing of the proposed approach shows that forecasting methods based on trend analysis can complement the existing tools of marketing and management of foreign economic activity, justify measures for the development of export market segments.
Baldzhy M. D. Forecast of the Export of Confectionery Products of Ukraine to food Markets / M. D. Baldzhy, O. Nosachenko, S. G. Nezdoyminov // International Journal of Agricultural and Statistical Sciences. – 2021. – Vol. 17, No.1. – Р. 187-196. DocID: https://connectjournals.com/03899.2021.17.187
Keywords: Confectionery industry; Cocoa and chocolate; Statistical methods; Forecasting; Trend analysis; Research Subject Categories::SOCIAL SCIENCES